Effectiveness and safety of combined treatment with herbal medicines and palliative chemotherapy for advanced gastric cancer: A systematic review and meta-analysis - Dong-Hyeon Kim; Soo-Dam Kim; Hyeong-Joon Jun; Eun-Bin Kwag; Sang-Won Shin; Hwa-Seung Yoo; So-Jung Park (Integrative Medicine Research)
Background: Advanced gastric cancer (AGC) is a leading cause of cancer-related death worldwide, and its treatment is complicated by challenges such as high recurrence rates, severe side effects, and the limited effectiveness of current therapies. Herbal medicine (HM) has emerged as an adjunct to palliative chemotherapy (PC), potentially improving the tumor response and reducing side effects. This study involved a meta-analysis to evaluate the effectiveness and safety of HM in palliative therapy for patients with inoperable stage III and IV AGC. Methods: Ten electronic databases, including PubMed, Embase, the Cochrane Library, CNKI, and ScienceON, were searched until August 2023. The inclusion criteria focused on randomized controlled trials (RCTs) that combined herbal medicine with palliative therapy for patients with AGC. The primary outcomes assessed were tumor response rates, overall survival, adverse drug reactions (ADRs), and patients' quality of life (QoL). Results: Our meta-analysis of the 101 included RCTs comparing PC alone to PC combined with HM revealed statistically significant improvements in the overall response rate (ORR), disease control rate (DCR), and survival rates, as well as a reduction in adverse drug reactions (ADRs) and an enhancement in the quality of life (QoL) of patients receiving HM in combination with PC (p < 0.00001, I² = 0%). Conclusions: The combination of HM with PC significantly increases tumor response and survival rates while reducing overall adverse drug reactions (ADRs) and improving the quality of life (QoL) of patients with stage Ⅲ and Ⅳ AGC. HMs not only improve the efficacy of PC but also help alleviate side effects, including myelosuppression, digestive symptoms, nausea, vomiting, diarrhea, liver and renal injuries, and neurotoxicity.Protocol registration: PROSPERO, CRD 42022354133.